Virtues as Qualities of Character: Alasdair MacIntyre and the Situationist Critique of Virtue Ethics. Issue 1 (17th February 2020) - Darr, Ryan
Abstract: Over the last two decades, a growing philosophical literature has subjected virtue ethics to empirical evaluation. Drawing on results in social psychology, a number of critics have argued that virtue ethics depends upon false presuppositions about the cross‐situational consistency of psychological traits. Alasdair MacIntyre's After Virtue has been a prime target for the situationist critics. This essay assesses the situationist critique of MacIntyre's account of virtue. It argues that MacIntyre's social teleological account of virtue is not what his situationist critics take it to be. Virtues, for MacIntyre, are not reducible to psychological traits. They are qualities of one's socially constituted character, and their intelligibility as virtues derives from their role in the narrative of one's life. Recognizing this both clarifies and complicates debates about the implication of situationist social psychology for virtue ethics. It also grants a new significance to MacIntyre's attention to the socio‐historical context of virtue, a significance that should be especially interesting to religious ethicists.